Новые подроды и виды палеарктических андрен (Hymenoptera, Andrenidae). Сообщение 1 - Осычнюк, А.З. (Вестник зоологии, 1993)
Two new Andrena F. subgenera arc established to include Middle Asian species: Longandrena subg. n. and Carinandrena stibg. n. 4 species of Andrena (Chlorandrena) are described as new: A. tirarli sp. n (Transcaucasia), A. luranica sp. n„ A. shteinbergi sp. n. and A. gloriosa sp. n. (Middle Asia). Type material is deposited in Institute of Zoology, Ukrainian Academy of Sciences (Kiev), Zoological Institute, Russian Academy of Sciences (St.-Petersburg), Zoological Museum, Moscow University.